Tempo, História e Educação Matemática - De Jesus Brito, Arlete [UNESP] (FapUNIFESP (SciELO), 2016)
In this paper, we discuss conceptions of time and historical changes of them. We analyze how these conceptions construct a social way of being, by education. We conclude the need for History of Mathematical Education researches about the use of the time in both educational laws and teaching of Mathematics. Our main references are Norbert Elias (1998), Michel Foucault (1993), Jacques Le Goff (1995) and Edward Thompson (1998).
Time, history, and mathematical education
Keywords: Education; History; Mathematics; Philosophy; Time